Otimização da configuração de parques hidrocinéticos: um estudo de caso com o Canal do Boqueirão - COSME, Diego Leonardo Santos (2024)
This study focuses on the energy characterization of the Boqueirão Channel through the measurement and analysis of its tidal currents. The data obtained were used to model the area in the DELFT3D-FLOW® software, adjusting the boundary conditions to ensure an accurate representation of the tidal currents. The theoretical energy potential, considering an area of 1.5 km2 within the channel, contemplates the installation of a hydrokinetic park with horizontal-axis turbines equipped with diffusers, where the interaction effects between wakes are evaluated using simplified models. In this analysis, the Levelized Cost of Energy for the hydrokinetic farm was studied, highlighting the feasibility and economic competitiveness of this renewable energy source. The results showed that the turbine model used for the simulation was based on a new methodology for designing diffused rotor blades, combining preliminary analyses in Computational Fluid Dynamics using the actuator disk and the geometric design of the rotor. This process considered the influence of blades on the flow, demonstrating consistency in 3D simulations, where the power coefficient peaks at the design condition (a peak power coefficient of 0.415 normalized by the largest cross-sectional area of the diffuser or 0.905 when normalized by the throat area). The analyzed arrangements indicated that lateral spacings of 1.5D and longitudinal spacings of 55D minimize interference between turbines and maximize the power coefficient of the downstream device.